Computed Tomography Assessment of Linear Splenic Dimensions and their Correlation with Anthropometric Measurements in Nepalese Population (Journal of Nobel Medical College, 2023)
Background: Geographical locations and ethnicity may influence variations in normal spleen dimensions, potentially leading to errors in assessment. This study aimed to correlate splenic dimensions with anthropometry and predict their variation with age and body surface area.Materials and Methods: Subjects (n=384) undergoing abdominal computed tomography were selected by random sampling. Splenic volume was calculated using the standard prolate ellipsoid equation. Correlation of splenic volume with body surface area and body mass index was done with Pearson’s correlation analysis. A multiple regression was run to predict splenic volume from age, height, and body surface area.Results: The mean age was 45±18 (range, 18-90 years). The mean splenic length, width, thickness, and volume were 7.6 ± 1.7 cm, 8.8 ± 1.5cm, 3.8 ± 0.9 cm, and 139 ± 58.2 cm3, respectively. The splenic width and splenic volume were significantly lower at extremes of age. A significant (P